2021
DOI: 10.1186/s12943-021-01358-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein encoded by circMAPK1 inhibits progression of gastric cancer by suppressing activation of MAPK signaling

Abstract: Background A novel type of noncoding RNA, circRNA has been reported to participate in the occurrence and development of diseases through many mechanisms. The MAPK pathway is a common signal transduction pathway involved in cell proliferation, inflammation and apoptosis and plays a particularly important role in cancers. However, the role of circRNAs related to the MAPK pathway in gastric cancer has not been explored. Methods A bioinformatics analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 47 publications
1
116
0
Order By: Relevance
“…The effect of NF-κB/MAPK pathway on the progression of pneumonia have been clearly revealed. [20][21][22] NF-κB pathway could serve as a potential target for the treatment of pneumonia. Several drugs have been used for treating pneumonia through targeting NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of NF-κB/MAPK pathway on the progression of pneumonia have been clearly revealed. [20][21][22] NF-κB pathway could serve as a potential target for the treatment of pneumonia. Several drugs have been used for treating pneumonia through targeting NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that the reduction of thyroid cells might be partly responsible for low thyroid hormone levels. Ras-Raf-MEK-MAPK signaling pathway was reported to be involved in numerous cellular and physiological processes essential to life including cell proliferation and cell growth [ 31 ]. The KEGG analysis of DMRs revealed that Ras and MAPK signaling pathways were dysregulated in high-glucose-cultured Nthy-ori3-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-503-3p in exosomes derived from bone marrow mesenchymal stem cells can increase the content of cancer stem cells in colorectal cancer, thereby promoting the growth of colorectal cancer ( 63 ). In addition to acting as competitive endogenous RNA, recent studies have found that circRNA with internal ribosome entry site (IRES) can bind to ribosomes and encode short peptides and proteins, thus directly regulating the function of tumor cells ( 64 ). Last but not least, as transcription factors or protein scaffolds, some circRNA interact directly with proteins to regulate the biological behavior of tumor cells ( 65 ).…”
Section: Discussionmentioning
confidence: 99%